2020
DOI: 10.1039/c9tc06571g
|View full text |Cite
|
Sign up to set email alerts
|

Non-toxic green food additive enables efficient polymer solar cells through adjusting the phase composition distribution and boosting charge transport

Abstract: Solvent additives play an important role in optimizing the morphology of the photoactive layer and improving the photovoltaic performance of polymer solar cells (PSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Since processing solvent additive with high boiling point was conducive to forming more ordered and nano-scaled bicontinuous interpenetration network structure which can improve the dissociation of light-induced exciton into the free charge carriers at the D/A interface and accelerate the transport of free charge carriers [85,86]. Hence, following that, we selected the 3% DIO (DIO/CB, V/V) as a solvent additive to proceed to optimize the device performance, as illustrated in Figure S12 (in Supplementary Materials).…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
“…Since processing solvent additive with high boiling point was conducive to forming more ordered and nano-scaled bicontinuous interpenetration network structure which can improve the dissociation of light-induced exciton into the free charge carriers at the D/A interface and accelerate the transport of free charge carriers [85,86]. Hence, following that, we selected the 3% DIO (DIO/CB, V/V) as a solvent additive to proceed to optimize the device performance, as illustrated in Figure S12 (in Supplementary Materials).…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
“…It indicates that methylation in central bithiazole has little influence on the molecular plane architecture. Both methylated SMAs also have a good planarity and strong intermolecular π-π stacking effect, which is available to facilitate charge transfer[38][39][40][41].However, smaller twist angle is observed in the BTz-4Cl-1 rather than BTz-4F-1 by theoretical calculation. It is suggested that high atomic mass halogens are available to improve the planarity and charge transport properties of conjugated materials through a heavy atom effect[42].…”
mentioning
confidence: 90%
“…Polymer solar cells (PSCs) have been emerged as one of the promising technologies for utilizing solar energy due to their advantages of flexibility, light weight, and possible semitransparence. [1][2][3][4][5][6][7][8][9][10][11] Typical bulk heterojunction (BHJ) PSCs, composed of one donor and one acceptor, have demonstrated power conversion efficiency (PCE) over 15% with the rapid development of high-performance donor and nonfullerene acceptor materials. [12][13][14][15][16][17] Although immense progress has been made, the inherent narrow absorption spectra of organic semiconductors makes it hard to harvest a large portion of incident photons in the solar spectrum, which hinders the photocurrent and the improvement of device performance.…”
Section: Doi: 101002/advs201903455mentioning
confidence: 99%
“…Polymer solar cells (PSCs) have been emerged as one of the promising technologies for utilizing solar energy due to their advantages of flexibility, light weight, and possible semitransparence. [ 1–11 ] Typical bulk heterojunction (BHJ) PSCs, composed of one donor and one acceptor, have demonstrated power conversion efficiency (PCE) over 15% with the rapid development of high‐performance donor and nonfullerene acceptor materials. [ 12–17 ]…”
Section: Introductionmentioning
confidence: 99%